1980
DOI: 10.1104/pp.65.6.1116
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Source-Sink Patterns by Modifications of Source Strength

Abstract: Bean plants, trimed to a simpl"id "double source, doube sink" translocatlon system (the paired primary leaves serving as the double source and the paired lateral laflets of the immature first trifolate leaf as the double sink) were used to study the magnitude and short-term time course of change in the alocatio ratio (parti ratio) of assimilates translocated from the labeled primary leaf to its respective "near" and "far leaflet" sinks in response to an increase or decrease in the source strength of the opposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…following treatment period 3, Table II, in Borchers-Zampini et al [2]) failed to increase the partition ratio even though PB rapidly recovered to near its predarkening rate (some recovery has been noted after about 4 h). A possibly related phenomenon is the observation by Borchers-Zampini et al (2) (Fig. 1, left) in response to exposure of leaf B for 2 h to a concentration of 3.0 ,ul/l SO2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…following treatment period 3, Table II, in Borchers-Zampini et al [2]) failed to increase the partition ratio even though PB rapidly recovered to near its predarkening rate (some recovery has been noted after about 4 h). A possibly related phenomenon is the observation by Borchers-Zampini et al (2) (Fig. 1, left) in response to exposure of leaf B for 2 h to a concentration of 3.0 ,ul/l SO2.…”
Section: Resultsmentioning
confidence: 99%
“…In the series B experiments, PB was altered by SO2 exposure of B rather than by varying the illuminance of B, as in the experiments by Borchers-Zampini et al (2). The rationale was otherwise similar.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Borchers-Zampini et al (6) have also demonstrated rapid changes in transport rates from source leaves following sink manipulation. The results reported here thus suggest that decrease in translocation out of source leaves is not directly linked to changes in CO2 assimilation, at least during the first few hours.…”
Section: Methodsmentioning
confidence: 97%
“…Experimental treatments such as partial shading or defoliation produce rapid changes in patterns and rates of translocation in sink regions (1,4,7). Changes in distribution of '4C-labeled material exported to sink regions monitored with a GM detector are observed to occur within tens of minutes; at this point changes in export may be inferred to occur.…”
mentioning
confidence: 99%